2008
DOI: 10.1007/s00261-008-9385-7
|View full text |Cite
|
Sign up to set email alerts
|

Thermal ablation: update and technique at a high-volume institution

Abstract: In the era of nephron-sparing surgery for small renal tumors, thermal ablation is gaining popularity. Both cryoablation and radiofrequency ablation have well-demonstrated short-term oncologic efficacy and safety. This article shares the current literature and the radiofrequency ablation technique at a high-volume institution. Cases are presented that illustrate solutions to obstacles frequently encountered during percutaneous ablation of renal masses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 46 publications
0
4
0
1
Order By: Relevance
“…Thermal ablation techniques such as radiofrequency ablation (RFA) and cryoablation have been used to treat renal tumors, and are usually performed under CT-guidance [1][2][3][4][5][6][7][8][9][10][11]. As intermediate to long-term data are emerging, results for percutaneous CT-guided RFA and cryoablation appear promising and show potential for treating renal tumors effectively [2][3][4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Thermal ablation techniques such as radiofrequency ablation (RFA) and cryoablation have been used to treat renal tumors, and are usually performed under CT-guidance [1][2][3][4][5][6][7][8][9][10][11]. As intermediate to long-term data are emerging, results for percutaneous CT-guided RFA and cryoablation appear promising and show potential for treating renal tumors effectively [2][3][4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 98%
“…In contrast to CT-guided RFA, during cryoablation, the effect of freezing (iceball formation) is clearly visualized in the tumor, renal parenchyma, and surrounding soft tissues using unenhanced CT scans. CT scanning is used during the procedure to plan the procedure, target the tumor with cryoablation probes, monitor the enlarging iceball, and survey the region after the ablation to ascertain whether the treatment is complete [2][3][4][5][6][7][8][9][10]. Typically, several CT scans are used to carry out these four phases of a cryoablation procedure [3,[5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Clinical study results have shown limitations of these therapies in larger tumors and suggest incomplete treatment, especially at the tumor margins (1)(2)(3)(4)(5)9). Methods to overcome this limitation have been explored in research.…”
Section: Animal and Tumor Modelmentioning
confidence: 99%
“…Experiments were performed in 28 athymic nude male rats (Hsd:RHFoxn1 rnu ; Harlan, Indianapolis, Ind) by R adiofrequency (RF) ablation and other thermal therapies are increasingly being used for focal tumor therapy in various organs, including the liver ( 1-3 ), kidneys ( 4,5 ), lungs ( 6 ), bone ( 7,8 ), and breasts ( 9,10 ). Clinical study results have shown limitations of these therapies in larger tumors and suggest incomplete treatment, especially at the tumor margins (1)(2)(3)(4)(5)9).…”
Section: Animal and Tumor Modelmentioning
confidence: 99%
“…Παράλληλα, οι κυτταρικές μεμβράνες αποσυντίθεται και προκαλείται καταστροφή του κυτταροπλάσματος. Ανάλογα με τη θερμοκρασία που αναπτύσσεται στην άκρη του ηλεκτροδίου μπορούμε να έχουμε και τα αντίστοιχα αποτε-λέσματα όπως διατομή, αιμόσταση ή απλή ενεργοποίηση των κυττάρων των υποκείμενων ιστών (εφαρμογές στην αισθητική ιατρική) (58)(59)(60)(61). Οι ραδιοσυχνότητες μπορούν να εφαρμοστούν σε διάφορους ιστούς αλλά η αποτελεσματικότητά τους εξαρτάται πάντα από τη σύσταση του ιστού.…”
unclassified